2004
DOI: 10.1146/annurev.earth.32.101802.120213
|View full text |Cite
|
Sign up to set email alerts
|

BIOGENIC MANGANESE OXIDES: Properties and Mechanisms of Formation

Abstract: ▪ Abstract  Manganese(IV) oxides produced through microbial activity, i.e., biogenic Mn oxides or Mn biooxides, are believed to be the most abundant and highly reactive Mn oxide phases in the environment. They mediate redox reactions with organic and inorganic compounds and sequester a variety of metals. The major pathway for bacterial Mn(II) oxidation is enzymatic, and although bacteria that oxidize Mn(II) are phylogenetically diverse, they require a multicopper oxidase-like enzyme to oxidize Mn(II). The oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
1,027
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 1,168 publications
(1,063 citation statements)
references
References 188 publications
32
1,027
2
2
Order By: Relevance
“…26,32,33 The oxides are also polycrystalline as proven by the appearance of distinct rings in the Fast Fourier Transform (FFT) of high-resolution images (inset in bottom in Figure 3). Chemical maps (energy dispersive X-ray spectroscopy, EDS) of the localization of Mn and U in the same area as an HAADF image (high angle annular dark field) show the colocalization of the two elements.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…26,32,33 The oxides are also polycrystalline as proven by the appearance of distinct rings in the Fast Fourier Transform (FFT) of high-resolution images (inset in bottom in Figure 3). Chemical maps (energy dispersive X-ray spectroscopy, EDS) of the localization of Mn and U in the same area as an HAADF image (high angle annular dark field) show the colocalization of the two elements.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…The addition or stimulation of Mn(II)-oxidizing bacteria has been proposed as a remediation strategy for some metals and organics (3). However, in the case of chromium, the hazard is increased in Mn(II)-oxidizing bacteria are a diverse group and found in almost all environments, but a single ecological advantage of Mn(II) oxidation has not been found (9,10). Hastings and Emerson (11) showed that bacteria oxidize Mn(II) up to five orders of magnitude faster than abiotic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Biogenic Mn oxides are poorly crystalline nano-size particulates with huge specific surface area and higher binging energy (Tebo et al 2004). Therefore, Cr(III) could be easily adsorbed on the surface of biogenic Mn oxide and then be oxidized.…”
Section: Discussionmentioning
confidence: 99%
“…Natural Mn oxides in the environment are believed to be derived either directly from biogenic Mn(II) oxidation or from the subsequent alteration of biogenic Mn oxides ( (Kim et al 2003); (Tebo et al 2004)). Mn oxidation in natural aquatic systems often proceeds at very slow rate if there is no participation of microorganisms (Nealson et al 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation